2016
DOI: 10.1111/myc.12539
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology reveals genetic diversity among 363 isolates of the Cryptococcus neoformans and Cryptococcus gattii species complex in 61 Ivorian HIV‐positive patients

Abstract: Cryptococcal meningitis is a severe opportunistic infection in HIV-infected patients. In Ivory Coast, despite the availability of antiretroviral treatment (ART), this infection is still prevalent. The study investigates the genetic diversity of 363 clinical isolates of Cryptococcus from 61 Ivorian HIV-positive patients, the occurrence of mixed infections and the in vitro antifungal susceptibility of the isolates. Serotyping was performed via LAC1 and CAP64 gene amplification. Genotyping was performed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 34 publications
1
24
1
Order By: Relevance
“…Different geographical locations can contribute to the epidemiological differences observed. This is further supported by the report of C. deutrogattii in Ivory Coast of which the isolate was susceptible to fluconazole [15]. To our knowledge, this case is only be the second in Africa and the first in East Africa [16], highlighting the possible underreporting of C. deuterogattii cases in Africa due to limited molecular diagnostics.…”
Section: Discussionsupporting
confidence: 79%
“…Different geographical locations can contribute to the epidemiological differences observed. This is further supported by the report of C. deutrogattii in Ivory Coast of which the isolate was susceptible to fluconazole [15]. To our knowledge, this case is only be the second in Africa and the first in East Africa [16], highlighting the possible underreporting of C. deuterogattii cases in Africa due to limited molecular diagnostics.…”
Section: Discussionsupporting
confidence: 79%
“…One patient was resampled in the 26 th week following a relapse. For each patient, the entire culture and five isolates of Cryptococcus were recovered as previously described [2931, 33]. Phenotypic characterization of the Cryptococcus species was achieved by chemotyping in L-canavanine-glycine-bromothymol blue (CGB) agar.…”
Section: Methodsmentioning
confidence: 99%
“…gattii species complexes from clinical sources in Yaoundé, Cameroon and Abidjan, and Ivory Coast and showed that C . neoformans (A, AFLP1/VNI) is widespread in the environment and is associated with the majority of cases of cryptococcosis in Ivory Coast [2931]. During these studies, the authors demonstrated that some patients suffered concurrent infections by different sero-genotypes, including mixed infections by two different Cryptococcus species, C .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Congo [ 32 ], and South Africa [ 56 ]. The species C. deuterogattii (genotype AFLP6/VGII) was reported causing cryptococcosis in HIV-positive patients from Ivory Coast [ 59 ]. In addition, C. tetragattii (genotype AFLP7/VGIV) was found to be a major cause of meningitis in HIV-positive patients in Zimbabwe [ 57 , 58 ] and was reported to cause cryptococcosis in patients from Botswana, Malawi, and South Africa [ 57 , 60 ].…”
Section: Cryptococcus Gattii Species Complex DImentioning
confidence: 99%